Understanding visitor travel behaviour in a nature-based tourism destination: Evidence from Gunung Stong, Malaysia - Nik Mohd Zainordin, Nik Mohamad Shamim; Ismail, An Nur Nabila; Rosely, Nurhidayah; Muhamad, Mira Qerul Barriah; Ahmad, Nur Azreen Farihah (Journal of Islamic, Social, Economics and Development, 2026)
Nature-based tourism destinations are increasingly promoted as instruments for sustainable regional development; however, effective planning requires a sound understanding of visitor travel behaviour. This study examines the travel behaviour of visitors to Gunung Stong, a prominent nature-based tourism destination in Malaysia, with the aim of providing evidence to support sustainable destination management. Using a quantitative survey approach, data were collected from 360 visitors and analysed using descriptive statistics. The analysis focused on key behavioural dimensions, including visit frequency, information sources, length of stay, purpose of visit, travel arrangements, and expectation fulfilment. The findings show that Gunung Stong is predominantly visited by first-time visitors who rely heavily on social media and word of mouth for travel information. Visits are mainly leisure-oriented, characterised by short stays and independent travel arrangements. Importantly, most visitors reported that their experiences met or exceeded expectations. These findings provide valuable insights for destination managers and policymakers in designing sustainable tourism strategies, particularly in managing visitor flows, strengthening digital communication, and enhancing nature-based experiences while minimising environmental impacts.